2019
DOI: 10.1080/13880209.2019.1672755
|View full text |Cite
|
Sign up to set email alerts
|

N-Butyrylated hyaluronic acid ameliorates gout and hyperuricemia in animal models

Abstract: Context: Hyaluronic acid (HA) plays critical roles in the structural skeleton, joint lubrication, renal function and cell signaling. We previously showed that partially N-butyrylated, low molecular weight, hyaluronic acid (BHA) exhibited an anti-inflammatory effect in cultured human macrophage, where inflammation was induced either by a TL-4 agonist or the low molecular weight HA itself, in dose-dependent fashion. Objectives: To investigate the anti-inflammatory, antioxidative, and antihyperuricemic effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 70 publications
(138 reference statements)
1
18
0
Order By: Relevance
“…Gout is a metabolic disorder of the purine accompanied by high levels of uric acid (UA) in the blood and the precipitation of sodium monourate crystals (monosodium urate (MSU)) in the joints and tissues. In the absence of treatment, progressive deterioration of the tissues and bones of the joints can occur, causing chronic synovitis, bone erosions, damage to the cartilage and tophi formation [114,115]. The work by Wang et al, shows that N-butyrylated HA (BHA) has an anti-inflammatory effect, leading to a reduction in joint swelling and a reduction in serum levels of IL-1β, IL-8, gamma interferon (IFN-γ) and monocyte chemoattractant protein 1 (MCP-1).…”
Section: Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Gout is a metabolic disorder of the purine accompanied by high levels of uric acid (UA) in the blood and the precipitation of sodium monourate crystals (monosodium urate (MSU)) in the joints and tissues. In the absence of treatment, progressive deterioration of the tissues and bones of the joints can occur, causing chronic synovitis, bone erosions, damage to the cartilage and tophi formation [114,115]. The work by Wang et al, shows that N-butyrylated HA (BHA) has an anti-inflammatory effect, leading to a reduction in joint swelling and a reduction in serum levels of IL-1β, IL-8, gamma interferon (IFN-γ) and monocyte chemoattractant protein 1 (MCP-1).…”
Section: Osteoarthritismentioning
confidence: 99%
“…The intraperitoneal injection of BHA suppressed UA production, reducing the activity of xanthine oxidase (XO, which catalyses UA production). BHA has been shown to exhibit anti-inflammatory, antioxidant and antihyperuricemic effects in vivo [115].…”
Section: Osteoarthritismentioning
confidence: 99%
“…Previous studies reported that glucosamine and chondroitin have demonstrated anti-inflammatory and anti-osteoarthritic effects [31,32]. Hyaluronic acid exhibited anti-inflammatory and antihyperuricemic effects in monosodium urate crystal-induced animal models for acute gouty arthritis and hyperuricemia [33]. The results of these studies show the potential usefulness of these components to prevent and treat hyperuricemia.…”
Section: Discussionmentioning
confidence: 63%
“…Studies have shown that gout caused by urate was mediated by the TLR4/NF-κB signaling pathway, and the IL-1β released was linearly related to it ( 20 , 21 ). Destruction of the intestinal barrier induced the translocation of gut-derived LPS from the gut to the liver, which increases the expression of inflammatory factors such as IL-1β and TNF-α in the liver ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%